Potential effectiveness of a surgeon-delivered exercise prescription and an activity tracker on pre-operative exercise adherence and aerobic capacity of lung cancer patients. (June 2021) - Finley, David J.; Stevens, Courtney J.; Emond, Jennifer A.; Batsis, John A.; Fay, Kayla A.; Darabos, Christian; Sacks, Olivia A.; Cook, Summer B.; Lyons, Kathleen Doyle
Abstract: Objectives: Pre-operative exercise may improve functional outcomes for lung cancer patients, but barriers associated with cost, resources, and burden make it challenging to deliver pre-operative exercise programs. The goal of this proof-of-concept study was to determine level of moderate-vigorous physical activity (MVPA) and change in aerobic capacity after participation in a home-based pre-operative exercise intervention. Materials and methods: Eighteen patients scheduled for surgery for suspected stage I-III lung cancer received an exercise prescription from their surgeon and wore a commercially-available device that tracked their daily MVPA throughout the pre-operative period. Descriptive statistics were used to calculate adherence to the exercise prescription. A one-sample t -test was used to explore change in aerobic capacity from baseline to the day of surgery. Results: Participants exhibited a mean of 20.4 ( sd = 46.2) minutes of MVPA per day during the pre-operative period. On average, the sample met the goal of 30 min of MVPA on 16.4% of the days during the pre-operative period. The mean distance achieved at baseline for the 6-min walk test was 456.7 m ( sd = 72.9), which increased to 471.1 m ( sd = 88.4) on the day of surgery. This equates to a mean improvement of 13.8 m ( sd = 37.0), but this difference was not statistically different from zero ( p = 0.14). Eight of the 17 participants (47%) demonstrated a clinically significant improvement of 14 m or more. Conclusion: A surgeon-delivered exercise prescription plus an activity tracker may promote clinically significant improvement in aerobic capacity and MVPA engagement among patients with lung cancer during the pre-operative period, but may need to be augmented with more contact with and support from practitioners over time to maximize benefits. Trial registration: The study protocol was registered with ClinicalTrials.gov prior to initiating participant recruitment (NCT03162718). Highlights: Clinicians need scalable and effective ways to promote exercise prior to surgery. A surgeon-delivered exercise prescription and activity tracker may promote exercise. Triage systems are needed to identify patients who need more support to exercise.